The development features of entrepreneurship in the Khatlon and Sughd regions of the Republic of Tajikistan - Kh. I. Aminov (Статистика и экономика, 2017)
The article analyzes the state and reveals development features of entrepreneurship in two major regions of Tajikistan – Khatlon and Sughd. The problems of entrepreneurship development in the spheres of industry, agriculture, trade, and services are identified. Special attention is paid to such indicators as the gross regional product, industrial and agricultural production, retail turnover, paid services, etc. The research hypothesis is that the level of entrepreneurship development is heterogeneous in the regions of the Republic of Tajikistan and the existing possibilities are not fully used.The theoretical and information basis of the study served the works of Tajik and foreign scientists in the field of entrepreneurship development, statistical compilations and data of the Agency on Statistics under President of the Republic of Tajikistan for the years 1991–2015. The obtained results allowed revealing a number of development features of entrepreneurship in the Khatlon and Sughd regions of Tajikistan. The analysis of the gross regional product shows that its value has increased several times since 2000, which was achieved due to the development of entrepreneurship. In 2015, 60% of the gross regional product was produced in Khatlon and Sughd regions. Despite the increase in the number of operating small enterprises, the number of joint ventures is decreasing. In this direction, it is necessary to intensify the entrepreneurship development through public-private partnerships. There are significant raw material and labor resources in the regions, which are not fully used. This is largely due to the lack of financial resources, the high cost of credit and high taxes. More attention should be given to these issues.It is noted that the entrepreneurship development in the regions of the country primarily depends on the energy development. There are huge hydropower resources in the regions, the use of which will give a significant impulse to the entrepreneurship development. The industries of the Khatlon region, developed in the early 1990s, are practically not working today. The same situation is observed in many branches of industry of the Sughd region. It is necessary to create conditions for the revival of industries.Despite the positive trends in the agriculture, there are different problems in the redistribution of the irrigated land, crop yields and productivity of livestock and poultry.There are still sectoral and regional problems in the more developed sectors of trade and services. Entrepreneurship in the sphere of trade and services is more developed in the Sughd region, as evidenced by the value of retail trade turnover and services rendered. It is necessary to develop a network form of trade in the sphere of trade. It is proposed to pay special attention to the entrepreneurship development in the sphere of tourism.The study shows that, despite the intensification of entrepreneurship development in the regions, there are still many problems. Further analysis of these problems will allow developing more targeted recommendations for the entrepreneurship development in the regions of the Republic of Tajikistan.